Influence of human activity patterns on epidemiology of plague in Western Usambara Mountains, Tanzania - Hubeau, Marianne; Gulinck, Hubert; Kimaro, Didas N.; Hieronimo, Proches; Meliyo, Joel (Tanzania Journal of Health Research, 2014)
Human plague has been a recurring public health threat in some villages in the Western Usambara Mountains, Tanzania, in the period between 1980 and 2004. Despite intensive past biological and medical research, the reasons for the plague outbreaks in the same set of villages remain unknown. Plague research needs to broaden its scope and formulate new hypotheses. This study was carried out to establish relationships between the nature and the spatial extent of selected human activities on one hand, and the reported plague cases on the other hand. Three outdoor activities namely, fetching water, collecting firewood and going to the market, were selected. Through enquiries the activity patterns related to these activities were mapped in 14 villages. Standard deviation ellipses represent the extent of action spaces. Over 130 activity types were identified and listed. Of these, fetching water, collecting firewood and going to the market were used for further analysis. The results indicate a significant correlation between the plague frequency and the size of these action spaces. Different characteristics of land use and related human activities were correlated with the plague frequency at village and hamlet levels. Significant relationships were found between plague frequency and specific sources of firewood and water, and specific market places.